Peptidomimetics as Potential Anti-Virulence Drugs Against Resistant Bacterial Pathogens - Martínez, Osmel Fleitas; Duque, Harry Morales; Franco, Octávio Luiz (Frontiers in Microbiology, 2022)
The uncontrollable spread of superbugs calls for new approaches in dealing with micro-bial-antibiotic resistance. Accordingly, the anti-virulence approach has arisen as an at-tractive unconventional strategy to face multidrug-resistant pathogens. As an emergent strategy, there is an imperative demand for discovery, design and development of anti-virulence drugs. In this regard, peptidomimetic compounds could be a valuable source of anti-virulence drugs, since these molecules circumvent several shortcomings of natural peptide-based drugs like proteolytic instability, immunogenicity, toxicity and low bioa-vailability. Some emerging evidence points to the feasibility of peptidomimetics to im-pair pathogen virulence. Consequently, in this review, we shed some light on the poten-tial of peptidomimetics as anti-virulence drugs to overcome antibiotic resistance. Specif-ically, we address the anti-virulence activity of peptidomimetics against pathogens’ se-cretion systems, biofilms and quorum-sensing systems.